The Royal College of Surgeons of England Damage Control Orthopaedic Trauma Skills course (DCOTS): resuscitative knowledge and confidence in surgical skills are reliably maintained at six months post course - Owen Bodger (The Annals of The Royal College of Surgeons of England, 2023)
Introduction: Since 2012, the Damage Control Orthopaedic Trauma Skills course (DCOTS) has trained more than 250 surgeons in the principles and practice of damage control orthopaedics and early appropriate care. This Royal College of Surgeons of England (RCS England) course takes place at the RCS England Partner cadaver laboratory at Brighton and Sussex Medical School. Trauma is a leading cause of morbidity and mortality in the UK, and the course has tried to pass on the lessons of war and conflict from its military faculty and hard-won lessons of “developed world” trauma from its experienced civilian faculty. Methods: Participating surgeons were invited to score their self-reported confidence before attending the DCOTS course, immediately afterwards and again 6 months later. A modified four-point Likert scale was used, with responses from 1 = No Confidence to 4 = Very Confident. Damage control resuscitation principles with damage control surgery showed the greatest retained increase at 6 months – 100% – which is extremely satisfying. Results: Self-reported confidence in pelvic external fixation was initially 93% dropping to 85%, which is also considered good to excellent. For pelvic packing, confidence was 90% at the end of the course, up from 19% precourse. This dropped to 62%, which was still considered good but low for the high standards of the course. This may relate to UK trainees’ lack of familiarity with the concept. Conclusions: Three of the main skills taught on the DCOTS are effectively retained at 6 months post course.